Development of an Ultrasonic System for Repelling and Detecting Rat Pests in Boarding Houses - Pratama, Rizki Wahyu; Habib, Syahlan; Prastia, Wahyu; Faisal, Muhammad Dimas; Pasaribu, Muhammad Fadly; Corio, Dean (Jurnal Teknologi Elektro, 2024)
This paper presents the development of an ultrasonic rat repellent device that integrates a Passive Infrared (PIR) sensor with an Arduino Uno microcontroller. The PIR sensor detects rat presence within a 5-meter range, transmitting this information to the Arduino Uno. In response, Arduino activates a buzzer to emit ultrasonic waves at frequencies specifically chosen to repel rats. The device also includes an LED as a visual indicator and an LCD for a real-time status display. The design incorporates jumper cables and a breadboard for assembling the circuit, with additional components, such as a potentiometer and battery connectors, for efficient operation. The effectiveness of the device depends on the precise programming of the Arduino, which controls the activation and intensity of ultrasonic emission. This innovative approach offers a noninvasive, environmentally friendly alternative for managing rat infestations in various settings.